1979
DOI: 10.1136/jnnp.42.9.831
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between plasma propranolol concentration and relief of essential tremor.

Abstract: SUMMARYThe relationship between plasma propranolol concentration and relief of essential tremor was examined in 11 patients during treatment with oral racemic propranolol in doses of 30 to 640 mg/day. Although propranolol decreased tremor in all 11 patients, the degree of improvement varied widely in individuals (mean 51%, range 25-90%), and was not related directly to the plasma propranolol concentration. In seven patients, optimum reduction in tremor occurred at plasma propranolol concentrations below 20 ng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…However, all these studies showed a great deal of interindividual variation, although results were reproducible within individual subjects. Of interest is that the maximum decrease in symptoms in patients with essential tremor appears to be concentration-dependent and also occurs at or below I OOngl ml (Jefferson et al, 1979;McAllister et aI., 1977).…”
Section: Therapeutic Plasma Levelsmentioning
confidence: 97%
“…However, all these studies showed a great deal of interindividual variation, although results were reproducible within individual subjects. Of interest is that the maximum decrease in symptoms in patients with essential tremor appears to be concentration-dependent and also occurs at or below I OOngl ml (Jefferson et al, 1979;McAllister et aI., 1977).…”
Section: Therapeutic Plasma Levelsmentioning
confidence: 97%
“…Propranolol has been effective in re ducing tremor in two thirds of the patients. For the remaining one third of the patients with severe essential tremor, stereotactic surgery re presents a valuable method to treat the disorder [6,10], …”
Section: Introductionmentioning
confidence: 99%
“…Twelve scales have been assessed for tremor evaluation ( [3,4,5,23,25,41,43,44,54,71,101,116] (Table 1), but only two of them, the FahnTolosa-Marin Tremor Rating Scale (FTM-TRS) and the Washington Heights-Inwood Genetic Study of Essential Tremor (WHIGET), reached recommendation status ( [23]. This scale also evaluates voice tremor as well as handwriting and other tasks, such as hygiene and dressing, assessing the impact of tremor on patients' daily life.…”
Section: Tremormentioning
confidence: 99%